Strategi Promosi Program Radio Trijaya melalui @mnctrijayafm - Wibowo, Jovan Raphael; Yoedtadi, Moehammad Gafar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
The development of information and communication technology over the past two decades has given rise to a new medium: social media. Social media facilitates communication and information dissemination, while also serving as a platform for education, entertainment, and business opportunities. These opportunities have encouraged companies, including Trijaya FM, to leverage social media. The author chose the use of Instagram (@mnctrijayafm) as a promotional medium for the radio's programs as the object of this study. The subjects of this research include a Social Media Specialist, a Trijaya Producer, and Trijaya listeners. This study examines Trijaya FM's marketing strategies using a qualitative approach with a case study method, referencing theories of strategy, marketing communication, promotion, and Instagram. The findings show that marketing strategies focusing on current issues and delivering engaging content on social media successfully captured the audience's attention, significantly increasing Trijaya FM's listenership. Media sosial memberikan kemudahan proses komunikasi dan penyebaran informasi serta menjadi sarana edukasi, hiburan, dan peluang bisnis. Salah satu radio, Trijaya FM, memanfaatkan media sosial Instagram (@mnctrijayafm) sebagai media promosi program radio. Penelitian ini bertujuan menjelaskan strategi pemasaran Trijaya FM menggunakan instagram @mnctijayafm. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, yang mengacu pada konsep strategi, komunikasi pemasaran, promosi, dan Instagram. Objek dalam penelitian ini adalah strategi komunikasi pemasaran yang dilakukan Trijaya FM dalam mempromosikan programnya, sementara subjek dalam penelitian ini adalah Trijaya FM. Spesialis media sosial, produser dan salah satu pendengar Radio Trijaya menjadi narasumber penelitian untuk menggali strategi pemasaran dalam memasarkan program radio. Hasil penelitian menunjukkan bahwa strategi pemasaran yang mengangkat isu terkini dan menyajikan konten menarik di media sosial berhasil menarik perhatian audiens sehingga meningkatkan jumlah pendengar Trijaya FM.